2020
DOI: 10.1002/jcp.29713
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine physiognomies of MSCs from varied sources confirm the regenerative commitment post‐coculture with activated neutrophils

Abstract: The interaction of mesenchymal stromal cells (MSCs) with paracrine signals and immunological cells, and their responses and regenerative commitment thereafter, is understudied. In the current investigation, we compared MSCs from the umbilical cord blood (UCB), dental pulp (DP), and liposuction material (LS) on their ability to respond to activated neutrophils. Cytokine profiling (interleukin‐1α [IL‐1α], IL‐2, IL‐4, IL‐6, IL‐8, tumor necrosis factor‐α [TNF‐α], interferon‐γ [IFN‐γ], transforming growth factor‐β … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 39 publications
0
10
1
Order By: Relevance
“…Here, a reactive oxygen species (ROS)-dependent mechanism was proposed. This is in contrast to a recent study, showing that neutrophils alter cytokine release by MSCs but not their osteogenic differentiation[ 38 ], suggesting that the activation status of the neutrophils is critical in this process.…”
Section: Role Of the Innate Immune Response In Fracture Healingcontrasting
confidence: 99%
“…Here, a reactive oxygen species (ROS)-dependent mechanism was proposed. This is in contrast to a recent study, showing that neutrophils alter cytokine release by MSCs but not their osteogenic differentiation[ 38 ], suggesting that the activation status of the neutrophils is critical in this process.…”
Section: Role Of the Innate Immune Response In Fracture Healingcontrasting
confidence: 99%
“…Immune infiltration is a feature of most cancers, and many cancers have a complex chemokine network that modulates tumor cell growth, survival and migration, as well as the extent and phenotype of this infiltration [ 26 , 27 ]. Neutrophils might play an essential role in tumor progression and development by providing a suitable microenvironment for their growth, thus serving as biomarkers for inflammation and as therapeutic targets [ 28 , 29 ]. On the other hand, tumor-associated macrophages (TAMs) promote tumor progression by providing nutrients for the invasion of tumor cells [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, TNF- α , a member of the TNF family, can bind to tumor necrosis factor receptor 1 (TNFR1) and TNFR2 receptors and exert two main effects upon binding, namely, mediating programmed cell death via the Fas pathway and maintaining cell growth by activating the transcription factors NF- κ B, activator protein 1 (AP-1), and mitogen-activated protein kinase (MAPK) [ 45 , 46 ]. In innate immune responses, activated neutrophils may induce MSCs to differentiate into osteoblasts by changing IL-1 α and TGF- β levels [ 47 ]. Some experiments have also shown that neutrophils inhibit the production of the extracellular matrix from MSCs and even induce MSC apoptosis by producing reactive oxygen species (ROS) [ 48 , 49 ].…”
Section: Osteoinductive Effects Of Immune Cells On Mscs For Bone Rege...mentioning
confidence: 99%